Targeting the Ghrelin Receptor as a Novel Therapeutic Option for Epilepsy - An Buckinx; Dimitri De Bundel; Ron Kooijman; Ilse Smolders (Biomedicines, 2021)
Epilepsy is a neurological disease affecting more than 50 million individuals worldwide. Notwithstanding the availability of a broad array of antiseizure drugs (ASDs), 30% of patients suffer from pharmacoresistant epilepsy. This highlights the urgent need for novel therapeutic options, preferably with an emphasis on new targets, since “me too” drugs have been shown to be of no avail. One of the appealing novel targets for ASDs is the ghrelin receptor (ghrelin-R). In epilepsy patients, alterations in the plasma levels of its endogenous ligand, ghrelin, have been described, and various ghrelin-R ligands are anticonvulsant in preclinical seizure and epilepsy models. Up until now, the exact mechanism-of-action of ghrelin-R-mediated anticonvulsant effects has remained poorly understood and is further complicated by multiple downstream signaling pathways and the heteromerization properties of the receptor. This review compiles current knowledge, and discusses the potential mechanisms-of-action of the anticonvulsant effects mediated by the ghrelin-R.